Concurrent Use of Hypnotic Drugs and Chinese Herbal Medicine Therapies among Taiwanese Adults with Insomnia Symptoms: A Population-Based Study. (23rd September 2013) - Lee, Kuei-Hua; Tsai, Yueh-Ting; Lai, Jung-Nien; Lin, Shun-Ku
Abstract : Background . The increased practice of traditional Chinese medicine (TCM) worldwide has raised concerns regarding herb-drug interactions. The purpose of our study is to analyze the concurrent use of Chinese herbal products (CHPs) among Taiwanese insomnia patients taking hypnotic drugs. Methods . The usage, frequency of services, and CHP prescribed among 53, 949 insomnia sufferers were evaluated from a random sample of 1 million beneficiaries in the National Health Insurance Research Database. A logistic regression method was used to identify the factors that were associated with the coprescription of a CHP and a hypnotic drug. Cox proportional hazards regressions were performed to calculate the hazard ratios (HRs) of hip fracture between the two groups. Results . More than 1 of every 3 hypnotic users also used a CHP concurrently. Jia-Wei-Xiao-Yao-San (Augmented Rambling Powder) and Suan-Zao-Ren-Tang (Zizyphus Combination) were the 2 most commonly used CHPs that were coadministered with hypnotic drugs. The HR of hip fracture for hypnotic-drug users who used a CHP concurrently was 0.57-fold (95% CI = 0.47–0.69) that of hypnotic-drug users who did not use a CHP. Conclusion . Exploring potential CHP-drug interactions and integrating both healthcare approaches might be beneficial for the overall health and quality of life of insomnia sufferers.